The Effect of Using instructional computerized software on Educational Achievement in the Computer Skills Course for Students with Special Needs (Deaf and Mute) in Primary Stage in Jerash Governorate, Jordan and Their Attitudes towards it - Al Atoum, Anas Mustafa; Siddiq, Mokhtar Othman (Arab Journal for Sciences and Research Publishing, 2016)
The study aimed to prepare, design and produce an instructional computerized software to the deafs and mutes students in the primary schools, the study aimed also to identify the impact of using instructional computerized software on checking homework lessons and remaining of the impact of learning and attitudes among deafs and mutes students in the basic level in subject of PC’s skills. The researchers had developed a study unit through programming PowerPoint PC program to the 1st level. Also he conducted a Pro & Pre Test then analyzed the study contents through designed a questionnaire to measure the role of PC and using PC Software and its impact on processes of learning and education among deafs and mutes students. The study conducted during the year (2012 – 2013) on deafs and mutes students at basic level withing the centers of Jerash for the special needs, the researcher followed the descriptive and analytical approach in additional to the experimental approach, the community sample consists of dump and deaf students at the basic level within the center of Jerash for the special needs, the total numbers of community sample were 120 students, among them (50) students of basic level were selected as a study sample and divided into two groups : one of them is experimental and the other is a control group. The study showed that there is a statistically significant at the level of ( P <0.05) to use PC in upgrading the ability of checking lessons of dump and deaf students at the basic level. The researcher recommended for providing a tutorial software in all instiututes and programs of those with special needs with full concentration on providing the modern tools that considered the easiness of using and effectiveness of performance, in addition to necesscity of training to the teachers who teaching students with special needs on using these tutorial software besides, providing a technology specialist to teach those with special needs in every institute.